A szegedi középkorász műhely 15 éve, 1992-2007 - Makk Ferenc (JATEPress Szeged, 2008)
The Szegedi Középkorász Műhely (henceforth: Workshop of Szeged Medievalists) as a civilian professional organisation came into being in the spring of 1992 with the leadership of Gyula Kristó, the most outstanding Hungarian medievalist. Professor Kristó coordinated the activities of the workshop until his untimely death at the beginning of 2004. In the first period the main task of the organisation was to provide opportunity for the members of the workshop to publish their books, because at the beginning of the 1990's Hungarian book publication as a whole collapsed. The series of books published by the workshop make up for the 'Szegedi Középkortörténeti Könyvtár' [The Szeged Library of Medieval History], in which members of the workshop have published 23 volumes (monographs and source publications) up to now. Later the workshop widened its activity to coordinate professional cooperation of its members for larger-scale undertakings (e.g. Korai Magyar Történeti Lexikon [Lexicon of Early Hungarian History]). Members of the workshop predominantly specialise in Hungarian prehistory and medieval history at the university (at several departments and research teams) as well as at the Teachers' Training School, Archive and Museum of Szeged. Apart from the Szeged members, several colleagues from Pécs and Budapest are affiliated to the Workshop. The most significant professional undertaking of the professional community of the Workshop is without doubt is the project entitled 'Anjou-kori oklevéltár' [Codex Diplomaticus Andegavensium]. In the framework of this project all the surviving documents (50-60 thousand charters) of the period of the Hungarian Anjou kings (I 301-1387) will be published in the form of excerpts. This involves research and publication of relevant 14th century sources of Hungarian and European history. This project, in which so far 22 volumes have been published, has already aroused a wide range of international interest. With this series medieval research in Szeged has come into the international forefront of source publication. The 'Codex Diplomaticus Andegavensium' will require many years of hard work from the scholars. That is why there is a tremendous need to train young scholar to ensure the future of this undertaking. Members of the Workshop take an active part in teaching students who specialise in Medieval Studies as well as in the Medieval PhD course, which started in 1994. Up to now, 26 students have defended their PhD theses, so taking this into consideration one can conclude that the Workshop is an acknowledged school of medieval scholars in Hungary. The professional output of the Workshop can be characterised by the fact that the members, whose volumes are published by other publishers as well, have written approximately 60 books as a result of their activity in the framework of the Workshop.
Keywords: Bölcsészettudományok; Történettudomány és régészet